Peran Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Pegawai pada PT. Perkebunan Nusantara IV Kota Medan - Eza Okhy Awalia Br Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Human resource management is an important factor that must always be considered in any business or organization. The foundation of human society is work ethic, or an employee's ability to make important decisions that can increase productivity or growth of a business. Research was conducted on PT staff. Perkebunan Nusantara IV Medan City. The aim of this research is to understand the role of human resource development in improving staff performance at PT. Perkebunan Nusantara IV Medan City. The analytical method used in this research is qualitative, namely data collection through observation and consultation with PT Perkebunan Nusantara IV Medan City. The research results show that human resource development has a positive and clear impact on employee productivity.